Hubungan Antara Konformitas Teman Sebaya dengan Pengambilan Keputusan Studi Lanjut Siswa SMP - Ulfah Alawiyah Mufida; Suharso Suharso; Zakki Nurul Amin (Indonesian Journal of Educational Counseling, 2022)
THE CORRELATION BETWEEN PEER CONFORMITY WITH FURTHER STUDY DECISION MAKING OF JUNIOR HIGH SCHOOL. This research was holded based on the phenomenon of Junior High School students who were less independent in further study decision making, so that they adapted based on peer conformity. The research aims to find out the relatonship between peer conformity with further study decision making in Junior High School students. This type of research is ex post facto quantitative with a correlational design. The samples of this research totaled 233 students from five schools with cluster sampling and proportional random sampling techniques. The instruments is used consisted of further study decision making scale, and peer conformity scale. Based on the result analysis, it showed that level further study decision making is high, level peer conformity is medium, and there is finded a negative and significant relationship between peer conformity and further study decision making (r=-0,364, p=0,000 < 0,05).